Game Ular Tangga untuk Pembelajaran IPA - Sylvia, Sylvia; Wuryastuti, Sri; Suratno, Tatang (Universitas Pendidikan Indonesia Kampus Serang, 2022)
This study Learning media is basically very important in the learning process. This is because learning media can make it easier for teachers to deliver subject matter and can create an effective and efficient learning process. The